Pengolahan Sampah Kota Terseleksi Menjadi Refused Derived Fuel Sebagai Bahan Bakar Padat Alternatif - Dwi Aries Himawanto; R. Dhimas Dhewangga P; Harwin Saptoadi; Tri Agung Rohmat; I Indarto (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
Municipal Solid Wastes (MSW) has great potential as a clean, renewable feedstock for producing modern energy carriers through thermochemical, called pyrolyis, and densification processes to form a Refused Derived Fuels (RDF), i.e MSW char briquette. In this article, thermogravimetry analysis has done to analyzed combustion characteristic of MSW briquette dan MSW char briquette. The sample in this research is 70 % wt MSW organic component 30 % wt MSW non organic component. . The 20 gram sample is placed in the furnace whose temperature is increased 10 0C/min and until sample temperature reaches 400 0C and held for 30 minutes before the sample is cooled into room temperature. 100 ml/min nitrogen is introduced from the bottom of furnace as a swept gas.. The formed char is densified and then characterized in a self manufactured macro balance, adopted from Swithenbank et al.. The 3 gram sample is placed in the furnace whose temperature is increased wih the selected heating rate until sample mass nearly constant.The results of the research showed that the effect of pyrolysis give the increase of sample heating value and give the lower ignition temperature of char briquette combustion.